Radiological Picture of Ocular Trauma in Ct-Scan of the Head with Orbital Centering: Literature Review - Fitri Nurul, Andi; Irsandy Syahruddin, Febie; Assagaf, Munjia (Jurnal Info Sains : Informatika dan Sains, 2025)
Ocular trauma is a leading cause of preventable vision impairment and blindness, with its incidence continuing to rise, including in Indonesia. Computed Tomography (CT-Scan) plays an important role in early diagnosis, injury assessment, and initial clinical decision-making for adult ocular trauma patients. This study aims to review the latest scientific evidence on the use of CT-Scan in managing adult ocular trauma using the PRISMA method. This is a systematic literature review covering sources from international databases and national journals (2020–2025). Of the 120 articles identified, 20 met the inclusion criteria and were analyzed narratively and descriptively. The results show that CT-Scan has high sensitivity in detecting orbital rupture, orbital fractures, intraocular foreign bodies, and vitreous hemorrhage. CT-Scan is also crucial in determining the Ocular Trauma Score (OTS) and visual prognosis, as well as aiding decision-making in emergency rooms and ICUs. Overall, CT-Scan is a fast, accurate diagnostic modality with significant prognostic value in managing adult ocular trauma